Sistem Pendukung Keputusan Untuk Menentukan Jurusan Terfavorit Dengan Menerapkan Metode SAW Studi Kasus SMKS Pembangunan Daerah Lubuk Pakam - Insan Astuti; Jijon Raphita Sagala (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2020)
The most favorite majors are things that must be determined by the school to choose or determine which department is the most favorite in the SMK Swasta Pembangunan Daerah Lubuk Pakam. Regional Development Vocational School. Each head of the department will improve the service and achievement of the department in order to be selected as the favorite department. The process of determining the favorite majors currently has weaknesses including it takes a very long time, using conventional or manual systems and decisions are only based on a meeting between the principal and related parties so that the results obtained are less accurate. Based on this, we need a computerized system, namely a decision support system to find out which department is the most favorite based on predetermined criteria. To determine the most favorite department, a computerized system is needed, namely a decision support system using the SAW method.The basic concept of SAW is to find a weighted sum of the performance of each alternative on all criteria, therefore this method is very suitable for the problems that exist in the SMK Swasta Pembangunan Daerah Lubuk Pakam.